Unraveling the Relationship Between Body Shame and Social Anxiety Among Young Adult Women - Zaidan, Nina Amalia (Program Studi Psikologi Fakultas Kedokteran Universitas Malikussaleh, 2024)
Body shame is shame on body image which involves a person's negative perception of a body shape or appearance that is considered unattractive by others and places himself in an unwanted position in the social environment. Body shame results in the emergence of social anxiety effects such as feeling embarrassed or doubtful in front of other people, feeling very afraid or worried that others will judge negatively or reject, and avoiding places where there are crowded people. The aim of this study is to determine the relationship between body shame and social anxiety in emerging adulthood. Respondents were obtained by using an online questionnaire with as many as 236 respondents with a non-probability sampling technique. Furthermore, body shame was measured by using the Body Image Shame Scale (BISS). Social Anxiety was measured by using the Social Avoidance Distress Scale (SADS). Meanwhile, the research data were analyzed by using Pearson product moment correlation test. The result of the correlation value (r) is 0.656 with significance (p) of 0.000. Thus, it can be concluded that there is a significant relationship between body shame and social anxiety in women in emerging adulthood.